Dampak Stres Kerja dan Disiplin Kerja terhadap Kinerja Pegawai RSUD Kota Bogor pada Masa Pandemi Covid 19 - Pahlawati, Enah; Norman, Efrita; Supriyatna, Rio Kartika; Hermaliana, Mia (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The purpose of this study was to determine and analyze the effect of work stress, work discipline on the performance of Bogor City Hospital employees during the Covid 19 pandemic and see the effect of work stress and work discipline simultaneously on the performance of Bogor City Hospital employees during the Covid 19 pandemic. This study using a sample of 60 respondents who are employees at the Bogor City Hospital as the object of research. The method of data collection was carried out directly by using questionnaires and interviews with employees of the Bogor City Hospital. From the results of data processing (output) obtained a correlation coefficient (R) of 0.795, it can be concluded that there is a strong or high relationship between work stress and work discipline on employee performance at the Bogor City Hospital. Then seen from the value of the coefficient of determination (R2) of 0.632 or 63.2%, it can be said that the percentage contribution of the influence of the independent variable (work stress and work discipline) on the dependent variable (employee performance) is 63.2% while the rest is 36.8 % influenced or explained by other factors not included in this model.